Biodegradation of low-density polyethylene by Microbulbifer hydrolyticus IRE-31. (1st June 2020) - Li, Zhongyu; Wei, Ren; Gao, Meixi; Ren, Yanru; Yu, Bo; Nie, Kaili; Xu, Haijun; Liu, Luo
Abstract: Polyethylene (PE) is one of the most widespread plastic materials. Nevertheless, due to its recalcitrance against biological degradation and the presence of toxic additives, landfilled and carelessly disposed PE products have caused serious pollution in the natural environments. In this work, we aimed to investigate the growth characteristics of Microbulbifer hydrolyticus IRE-31 and its application in the biological degradation of low-density PE. The IRE-31 strain was isolated from marine pulp mill wastes rich in lignin which is a natural complex polymer containing also saturated carbon-carbon bonds like in PE. Following 30 days cultivation of the IRE-31 strain, the biodegradation of linear low-density PE particles was evidenced clearly by morphological changes of the polymer surface monitored by scanning electron microscopy and the formation of additional carbonyl groups in the polymer chains indicated by Fourier transform infrared spectroscopy. Highlights: The degradation of polyethylene by a marine strain Microbulbifer hydrolyticus IRE-31 was observed by SEM and FTIR analysis. The marine bacteria M. hydrolyticus IRE-31 shows potential to break down plastics in the ocean. Phylogenetic analysis of M. hydrolyticus IRE-31 shows a close relationship with several known plastic degrading bacteria.